ON THE JOB TRAINING DAN OFF THE JOB TRAINING KARYAWAN PT. AMIR HASAN MEDAN - DEWI ANGGRAINI; DENNIUS .; ARWIN .; ELSERRA SIEMIN CIAMAS; WILINNY . (LP2MTBM MAKARIOZ, 2019)
The objective of research is to known employee training at PT. Amir Hasan Medan. The Grand Theory in this research usingTriton theory (2010:107) explain that human resource training base on the place of execution can be classified into : on thejob training and off the job training. This research using descriptive qualitative research method. Data collection methodcollected by Structure Interview. Meanwhile, data analysis method using Miles and Huberman Method, consisting of datareduction, data display, and conclution drawing / verification. The conclution of research shown employee training thatapplied in PT Amir Hasan Medan, covers : On the job training which is Direct Practice and Off the job training wich isLecture. Direct Practice method apply for the new employee. The new employees will be supervised by the senior employeein two until three weeks for them to learn that new jobs. Lecture training method that held on a class meeting and for theSales Division only. In this class meeting, lead by a Manager or a Head of Sales division that give the tecniques ofmarketing such as communication tecnique, Custommer approching tecnique, closing deal tecnique, and ect. Theparticipant of this training is an Employee that the Sales was decreasing, this apply for once in a month.